Multiculturalism and international law: essays in honour of Edward McWhinney - Yee, Sienho (Martinus Nijhoff Publishers, 2009)
Multiculturalism and general theories of international law -- Multiculturalism and international organizations and courts -- Multiculturalism and the progressive development in substantive international law
Includes bibliographical references and index. - Most essays in English, three essays in French. - Description based on print version record
Keywords: Electronic books; Festschrift; Aufsatzsammlung; Internationales Recht; Menschenrecht; Minderheitenrecht; Multikulturelle Gesellschaft